Regulaç\~ao e investimento no setor de saneamento no Brasil: Trajetórias, desafios e incertezas - Gesmar Rosa dos Santos; Julio Issao Kuwajima; Adrielli Santos de Santana (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This paper describes and analyzes the trajectory of water and sanitation policies in Brazil, with emphasis on the Union acts on financing and regulation evolution in the sector. The objective is to point the different regulatory forms and models already tried, as well as to highlight the different forms of action of the State and the private sector and to discuss remaining challenges. The difficulties to overcome low regional rates of coverage of water supply services and, mainly, sanitary sewage that are listed on the Plano Nacional de Saneamento Básico (Plansab), Sistema Nacional de Informaç\~oes sobre Saneamento (SNIS) and Pesquisa Nacional por Amostra de Domicílios Contínua (PNAD Contínua). We highlight the central elements and perspectives in face of current scenario of changes in Law 11445/2007, which provides guidelines, instruments and ways to finance services, giving water and sewage services a status of the infrastructure and health sectors. Among the conclusions we point: the recent advances in state and municipal regulation; advances and uncertainties in the changes in the regulatory framework under implementation; and the tendency to increase the weight of the tariff to investments. Suggestions are presented to improve the sanitation policy and its instruments, as well as for regulation and State investments in the sector.
Keywords: L50; Q25; Q28; 330; water; sanitary sewage; regulation; financing; health